2012
DOI: 10.1021/es203878c
|View full text |Cite
|
Sign up to set email alerts
|

U(VI) Sorption and Reduction Kinetics on the Magnetite (111) Surface

Abstract: continuous batch-flow conditions. We observed, in real-time and in situ, adsorption and reduction of U(VI) and subsequent growth of UO 2 nanoprecipitates using atomic force microscopy (AFM) and newly developed batch-flow U L III -edge grazing-incidence x-ray absorption spectroscopy near-edge structure (GI-XANES) spectroscopy. U(VI) reduction occurred with and without CO 3 present, and coincided with nucleation and growth of UO 2 particles. When Ca and CO 3 were both present no U(VI) reduction occurred and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 46 publications
4
75
0
Order By: Relevance
“…As shown in (Fig. 6,11 Structural Fe(II) was identied as a stronger reducing agent with E 0 ¼ À0.65 V to À0.34 V. 37 The kinetics results revealed that reduction rates of U(VI) on M-rGO were slower than removal rates. It can be seen that the sorption process was the predominant U(VI) removal mechanism by M-rGO.…”
Section: Reaction Kineticsmentioning
confidence: 94%
See 1 more Smart Citation
“…As shown in (Fig. 6,11 Structural Fe(II) was identied as a stronger reducing agent with E 0 ¼ À0.65 V to À0.34 V. 37 The kinetics results revealed that reduction rates of U(VI) on M-rGO were slower than removal rates. It can be seen that the sorption process was the predominant U(VI) removal mechanism by M-rGO.…”
Section: Reaction Kineticsmentioning
confidence: 94%
“…4,5 More importantly, as the naturally occurring minerals composed of Fe(II) and Fe(III), magnetite was evidenced to reduce U(VI) to U(IV) by the oxidation of Fe(II). 11 However, the magnetic particles are difficult to use in continuous ow system because they are instability and susceptible to agglomeration and oxidation. [8][9][10] Further evidence indicated that the redox transition of U(VI) occurred aer U(VI) was adsorbed on the surface of magnetite.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for the initial decrease is most probably reduction of U(VI) to U(IV) by Fe(II), which has been observed before in a number of studies [24][25][26] for both solid Fe(II) phases as well as Fe 2+ in solution.…”
Section: Uranium In Solutionsupporting
confidence: 53%
“…It has been suggested to proceed via the transfer of a single electron to U(VI), producing U(V), followed by the disproportionation of U(V) to U(IV) and U(VI) (29,30). However, there is also evidence that direct reduction to U(IV) occurs and is accompanied by the release of Fe(II) into solution (31). The discrepancy in reduction mechanisms observed among studies is likely due to the fact that control on the extent of U(VI) reduction is wrought by the combination of two competing factors: the Fe 2+ /Fe 3+ ratio at the surface of iron minerals and the U coordination environment (32).…”
Section: Discussionmentioning
confidence: 99%